Manila by night, [or] City after dark - Bernal, Ishmael; Solis, Charito; Moreno, Alma.; Tolentino, Lorna; Unico Entertainment, LLC.; Regal Home Video (Firm). ([Philippines?] Regal Home Entertainment, 2006)
An ensemble of desperate characters are trapped between the city's lure of a better life and its dark and ghastly ways of providing for its residents. The impoverished women pin their hopes on the city and the men lure them into prostitution, drugs and crime. Ironically, while they seem to ruin one another's lives, they also become each other's best chances for hope and survival. The drug-pushing lesbian played by Cherie Gil finds solace in the blind sauna bath employee played by Rio Locsin who in turn is led across the dismal streets of Manila by the gay couturier played by Bernardo Bernardo. "Manila by night" a.k.a. "City after dark" is a keen look into the social problems affecting Manila's underworld. With its controversial bold visual imagery, it is a brilliant reflection of the reality that the Filipino has yet to confront.
Title from container.
Originally released as a motion picture in 1980.
Editor, Augusto Salvador.
Charito Solis, Alma Moreno, Lorna Tolentino, Rio Locsin, Cherie Gil [and others].
DVD, region 1; Dolby Digital; NTSC.
Tagalog dialogue, with English subtitles.
Keywords: Prostitutes -- Philippines -- Manila -- Drama; Crime -- Philippines -- Manila -- Drama; Drug abuse -- Philippines -- Manila -- Drama; Feature films -- Philippines